Use of increased reality as a support tool in physics teaching in Baccalaureate - NÁlava, Alex Paúl Zambrano; Martínez, María Elena Moya (International Journal of Psychosocial Rehabilitation, 2020)
In today's society integrated globally by globalization, the widespread use of digital media and resources, education becomes a fundamental part of this gear to understand technologies of information and communication as its corresponding application. It is a valuable opportunity for teachers to make use of a variety of technological tools to achieve an improvement in the teaching-learning process and promote the development of the individual in their autonomous study. This article analyzes the use of augmented reality to support the teaching-learning process in secondary education, emphasizing the subject of Physics, taking into consideration the variety of media, platforms and technological devices present in most classrooms and homes. , which can be used to facilitate the teaching of the subject under consideration. The objective is to analyze, how to substantiate the importance of augmented reality applied in education as a support in the teaching-learning process, obtaining results through bibliographic and exploratory research in specialized and indexed journals, the respective databases and references verified from the internet, also using the descriptive, inductive-deductive and comparative method which allow us to reach the final conclusions.